Effect of wastes from sugar cane industry on the mechanical and hydraulic properties of pervious concrete - da Silva, R. G. [UNESP]; Bortoletto, M. [UNESP]; Bigotto, S. A.M. [UNESP]; Akasaki, J. L. [UNESP]; Soriano, L.; Tashima, M. M. [UNESP] (Taylor & Francis, 2021)
Pervious concrete is a construction material widely used in pervious pavements. Pozzolanic materials replacing partially Portland cement can improve mechanical and hydraulic issues associated with the use of pervious concrete. This paper reports the use of wastes from the sugar cane industry (sugar cane bagasse ash and sugar cane straw ash) and their influence on the mechanical and hydraulic properties of pervious concrete for different binder:aggregate mass ratio (1:3.5, 1:4.0, 1:4.5, 1:5.0). The assessed pervious concrete achieved a compressive strength in the range 7.4–14.2 MPa, a total porosity between 26.4 and 32.4% and an infiltration rate of 0.6–1.3 cm/s.
Keywords: Pervious concrete; pozzolans; sugar cane bagasse ash; sugar cane straw ash